The new encyclopaedia Britannica. - Encyclopaedia Britannica, inc. (Chicago, Ill. : Encyclopaedia Britannica, 1990)
Combines topics with over 238 years of expertise. This title provides both facts as well as articles on various subjects. It features images of art, geography, science, sports, and more. It includes photographs, illustrations, maps, charts, and diagrams.
Includes bibliographical references and index
kjo 22/10/2018
Ref
Keywords: Encyclopedias and dictionaries